2014
DOI: 10.2147/bs.s75573
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical and functional characterization of a biosimilar adalimumab ZRC-3197

Abstract: ZRC-3197 has been developed indigenously by Cadila Healthcare Ltd as a biosimilar adalimumab of originator HUMIRA ®. Biosimilarity has been demonstrated with a comprehensive set of state-of-the-art analytical techniques to characterize the physicochemical and functional properties of ZRC-3197 in comparison with originator HUMIRA ®. The biosimilar ZRC-3197 showed indistinguishable primary and secondary structures with similar level of purity and heterogeneity as compared to that of the originator product. When … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 19 publications
3
20
0
Order By: Relevance
“…Cadila Healthcare Limited of the Zydus Group has developed an adalimumab biosimilar (Exemptia; ZRC‐3197). Extensive physicochemical and biological comparability data showed the test adalimumab (Exemptia) to be highly similar to the reference adalimumab …”
Section: Discussionmentioning
confidence: 97%
“…Cadila Healthcare Limited of the Zydus Group has developed an adalimumab biosimilar (Exemptia; ZRC‐3197). Extensive physicochemical and biological comparability data showed the test adalimumab (Exemptia) to be highly similar to the reference adalimumab …”
Section: Discussionmentioning
confidence: 97%
“…28 The primary and secondary structures of ZRC3197 and reference adalimumab are identical, and no differences were detected in aggregation or in the profile of lowmolecularweight fragments between these two biopharma ceuticals. 29 Charge heterogeneity, glycan profiles and other posttranslational modifications were also highly similar between ZRC3197 and reference adalimumab. Functional properties, including affinity for TNF and FcγRIIIa receptors and in vitro TNFneutralizing activity, were also highly similar.…”
Section: Bow015mentioning
confidence: 76%
“…A comparative toxicology study conducted in animals showed no significant differences between ZRC3197 and reference adalimumab in vivo. 29 The Cadila Healthcare Laboratory (India) conducted a clinical trial in India that compared ZRC3197 and ref erence adalimumab in 120 patients with RA. The results of this trial have not been published in a peerreviewed journal nor have they been presented at a major meeting in abstract form.…”
Section: Bow015mentioning
confidence: 99%
“…Exemptia™ ( Cadila Healthcare ) Bandyopadhyay and coworkers [40] reported on the physicochemical properties and in vivo pharmacokinetic and toxicology profile of Exemptia™ in the journal Biosimilars and concluded that the molecule displayed highly similar characteristics to adalimumab. It should be noted that studies from non-indexed publications were not included in this review, and therefore the data from this publication were not extracted.…”
Section: Resultsmentioning
confidence: 99%